Experimental ion mobility measurements in Xe-CH4. (4th September 2017) - Perdigoto, J.M.C.; Cortez, A.F.V.; Veenhof, R.; Neves, P.N.B.; Santos, F.P.; Borges, F.I.G.M.; Conde, C.A.N.
Abstract: Data on ion mobility is important to improve the performance of large volume gaseous detectors. In the present work, the method, experimental setup and results for the ion mobility measurements in Xe-CH 4 mixtures are presented. The results for this mixture show the presence of two distinct groups of ions. The nature of the ions depend on the mixture ratio since they are originated by both Xe and CH 4 . The results here presented were obtained for low reduced electric fields, E / N, 10–25 Td (2.4–6.1 kV ⋅ cm −1  ⋅ bar −1 ), at low pressure (8 Torr) (10.6 mbar), and at room temperature.